Peran Guru dalam Meningkatkan Maharah Kalam Siswa di Madrasah Tsanawiyah Nurul Hikmah Haurgeulis - Supriadi Supriadi; Ahmad Asrof Fitri; Moch. Hasyim Fanirin (Departement of Mathematics Education, 2023)
MTs Nurul Hikmah Haurgeulis is determined to implement decentralization in the field of education, which is essentially based on empowering its own resources and as part of the national education system, it certainly feels obligated to always improve the quality and quantity of graduates. The purpose of this study was to find out the teacher's role in increasing the maharah kalam of MTs Nurul Hikmah Haurgeulis Indramayu students, and to find out what supporting and inhibiting factors the teacher had in an effort to increase the maharah kalam of students at the madrasah. This study uses a qualitative descriptive approach with the research subject being an Arabic teacher. In collecting data, the authors use observation and documentation techniques. In analyzing research data, the authors draw conclusions by inductive way. The results of this study indicate that the teacher's role in improving the maharah kalam of MTs Nurul Hikmah Haurgeulis Indramayu students is: a) the teacher as a teacher in the process of learning Arabic, b) the teacher as a guide helping students who have difficulty understanding Arabic learning, c) the teacher as class managers who can see the situation and condition of students so they don't feel bored in participating in learning Arabic. The conclusion is that the teacher's role as teacher, mentor, and class manager in learning Arabic requires the fulfillment of several pedagogic competencies and the potential of Arabic language.